Recent advances in two-dimensional magnets : physics and devices towards spintronic applications - Ningrum, Vertikasari P. (2020)
The emergence of low-dimensional nanomaterials has brought revolutionized development of magnetism, as the size effect can significantly influence the spin arrangement. Since the first demonstration of truly two-dimensional magnetic materials (2DMMs) in 2017, a wide variety of magnetic phases and associated properties have been exhibited in these 2DMMs, which offer a new opportunity to manipulate the spin-based devices efficiently in the future. Herein, we focus on the recent progress of 2DMMs and heterostructures in the aspects of their structural characteristics, physical properties, and spintronic applications. Firstly, the microscopy characterization of the spatial arrangement of spins in 2D lattices is reviewed. Afterwards, the optical probes in the light-matter-spin interactions at the 2D scale are discussed. Then, particularly, we systematically summarize the recent work on the electronic and spintronic devices of 2DMMs. In the section of electronic properties, we raise several exciting phenomena in 2DMMs, i.e., long-distance magnon transport, field-effect transistors, varying magnetoresistance behavior, and (quantum) anomalous Hall effect. In the section of spintronic applications, we highlight spintronic devices based on 2DMMs, e.g., spin valves, spin-orbit torque, spin field-effect transistors, spin tunneling field-effect transistors, and spin-filter magnetic tunnel junctions. At last, we also provide our perspectives on the current challenges and future expectations in this field, which may be a helpful guide for theorists and experimentalists who are exploring the optical, electronic, and spintronic properties of 2DMMs.